Cutibacterium acnes Prosthetic Joint Infections: Is Rifampicin-Combination Therapy Beneficial? - Grégoire Saltiel; Vanina Meyssonnier; Younes Kerroumi; Beate Heym; Olivier Lidove; Simon Marmor; Valérie Zeller (Antibiotics, 2022)
No consensus has been reached on the optimal antibiotic regimen to treat Cutibacterium acnes PJIs (Ca-PJIs). In vitro studies showed excellent rifampicin efficacy against biofilm-associated C. acnes infections, but clinical studies did not confirm the superiority of rifampicin-combined therapy over monotherapy. This prospective cohort study was undertaken to analyze the outcomes of 70 patients who underwent exchange arthroplasty for chronic monomicrobial Ca-PJI and were treated with rifampicin or without between 2004 and 2019. The 37 patients treated from January 2004 to August 2014 were prescribed rifampicin-combination therapy and the 33 treated from September 2014 to December 2019 received monotherapy without rifampicin. The primary endpoint was the 2-year Kaplan–Meier-estimated reinfection-free probability, including relapses and new-pathogen PJIs. The 2-year reinfection-free rate was high and not different for patients who had received rifampicin or not (89.2% vs. 93.8%, respectively; p = 0.524). None of the patients relapsed and six developed new-pathogen PJIs. Our results do not support a benefit of rifampicin-combination therapy for patients who underwent exchange arthroplasty for chronic Ca-PJIs.